The effect of injection timing on the performance of natural gas with a high carbon dioxide (CO2) content in a Direct Injection (DI) gas engine - Wasiu, A.B. (EDP Sciences, 2014)
This paper investigates the potential of utilizing raw natural gas from its reserves in Malaysia which are not harnessed because they are uneconomical due to the presence of large CO2 in it ranging from 25 to 89. For this experimental work, the natural gas fields were simulated by adding CO 2 at 10, 20, 30, and 40 to pure natural gas, and tested in a single-cylinder spark-ignition direct injection (DI) compressed natural gas (CNG) engine. Various injection timings were used, the injection duration was maintained, the ignition timing was adjusted to obtain the maximum brake torque (MBT), and at wide open throttle (WOT). The tests were carried out at a constant engine speed to study the effect of injection timings on performance and emission of the engine. Experimental results show that generally, the presence of high carbon dioxide content in the natural gas reduces the heating value of the mixture when compared with pure natural gas but however could be enhanced with injection timing in the range of 120 and 180 particularly for 20 CO 2 proportion in the mixture. There was a reduction in the NOX and CO emissions but an increase in the unburnt hydrocarbons (THC). Â© 2014 Owned by the authors, published by EDP Sciences.